Deceleration in Female Labor Force Participation in Latin America - Gasparini, Leonardo Carlos (2017)
After half a century of sustained growth, female labor force participationhas decelerated in Latin America, especially among married vulnerablewomen. Based on a large database of microdata from household surveysthis paper documents this recent deceleration and provides evidence onthe determinants. We argue that the fast economic growth experiencedby the region in the 2000s was an important driving force: lowerunemployment and higher earnings of male partners plus increasedsocial assistance may have reduced the pressing need for vulnerablewomen to take low quality jobs